(untitled) (Research, Society and Development, 2021)
Cancer is a disordered proliferation of cells in a tissue or organ that can be triggered by external and internal factors. Antineoplastic treatment is divided into surgery, radiotherapy and chemotherapy, and can be used alone or in combination. Radiotherapy and chemotherapy cause adverse effects in the patient’s oral cavity, such as xerostomia, oral mucositis, trismus, dysphagia, odynophagia, candidosis, radiation-related caries and osteoradionecrosis. It is necessary for the dental surgeon to know how to design the best prevention, diagnosis and treatment protocol individually to obtain the desired results. The objective of this work is to show the importance of the dental surgeon in the multidisciplinary team and that their role is essential in monitoring before, during and after the patient is undergoing antineoplastic treatment, providing preventive and therapeutic care, with the aim of improving quality of life and with pain and symptom relief. This is a literature review with bibliographic searches in scielo and pubmed databases with articles between 1993 and 2021. It was evident in this study that the dental surgeon plays a preponderant role in patient care and chemotherapy as these treatments can affect the oral cavity and together with a multidisciplinary team has the function of offering an improvement in the patient’s quality of life and care before, during and even after anticancer treatment. It is necessary that the dental surgeon has adequate knowledge for the management and care of cancer patients.